Pengaruh Penggunaan Tekonologi Informasi, Efektivitas Sistem Informasi Akuntansi dan Kepercayaan Atas Sistem Informasi Akuntansi Terhadap Kinerja Karyawan PT. Bank Pembangunan Daerah Jawa Tengah Kantor Cabang Cilacap - Burhanudin, Hafiz Rizal Zaman, Drs. Wahyono, Ak, MA (2016)
The aimed of this study is to find out the effect of the use of information technology, effectiveness of accounting information system, trust to the accounting information system on the staff's performances. The study was conducted at PT. Bank Pembangunan Daerah Jawa Tengah branch offices Cilacap. The sampling method used was total sampling. The number of samples collected as many as 50 staffs. The data analyzed using multiple regression analysis technique. The results of this research showed that the use of information technology, effectiveness of accounting information system, trust to the accounting information system have effect on the staff's performances.